Intervención de enfermería para la recuperación de la salud individual de pacientes post covid en el centro de salud de santa rosa - Calapucha Mamallacta, Klenger Xavier (2025)
This study focuses on the nursing intervention for an individual’s health recovery for post-COVID patients at the Santa Rosa Health Center, Riobamba-Ecuador. Propose a practical clinical guide to nursing interventions for the recovery of the individual health of post-COVID patients initiating with the nursing staff. The proposed methodology, which combines qualitative and quantitative approaches, reflects a comprehensive approach to understanding and addressing the challenges associated with post-COVID care, providing a complete view of the situation and strategies for patient recovery highlighting the fundamental contribution of nursing staff in the prevention and early detection of complications. The effectiveness of interventions based on Jean Watson's model is highlighted to increase knowledge about the prevention and treatment of COVID and post-COVID patients, providing possible solutions to social, physical and informational problems associated with post-COVID. In conclusion, it is suggested to constantly hold talks, workshops or conferences in order to inform and improve care.